The Construction of the Reality of Coverage Media Television about the Islamic Defenders Front - Puji Santoso; Syukur Kholil; Syafruddin Pohan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The aim of this research is to analyze how the three national news television stations, MetroTV, KompasTV, and TVOne, tend to construct the news reality about Islamic organizations of Islamic Defenders Front in the period 2016-2017. The research method focuses on gathering, analyzing media content (framing studies), and mixing quantitative and qualitative data in one study or series of studies. The main premise is the use of mixed quantitative and qualitative approach, by providing an understanding of better research problems because it uses two approaches at once. The main instrument in this research was the researchers themselves who collected data through websites from three selected television media, in-depth interviews, participatory observation, and carried out relevant documentation studies related to objects of the research such as literature, BlogSpot, internet (online), e- journals, and reports of similar research results that are considered relevant. The results of this research show that the three news television stations studied, there were MetroTV, KompasTV, and TVOne has carried out construction on all the news that entered the newsroom, including news about the Islamic Defenders Front (FPI). Constructivist approaches assess that partiality and certain values cannot be eliminated from media coverage. Ethics, moral choice, and journalist and media alignments are the integral parts of news production. Ethics and morals in many ways mean partiality to one group or partiality to certain values. And it is generally based on certain beliefs as well. In addition, there were framing models that tended to be carried out by MetroTV, KompasTV, and TVOne. The framing model that tends to be carried out by the three news television media also tends to be different. From the models, the message and meaning are different from the audience or television viewers.